Wafer support

By using a wafer support with a boron nitride substrate and a aluminum nitride protective layer, the corrosion problem of corrosive gases and plasma on the wafer support is solved, and higher corrosion resistance and heat impact resistance are achieved, particle generation is reduced, and the stability of semiconductor manufacturing and equipment life are improved.

CN120569358APending Publication Date: 2025-08-29FERROTEC CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380089650.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-03
Filing Date
2023-12-25
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

In the semiconductor manufacturing process, existing wafer support is susceptible to corrosive gases and plasma environment, resulting in the production of particles, affecting the stability of the manufacturing process and equipment life.

Method used

A cuttingable ceramic containing boron nitride is used as a base material, and a ceramic sintered body protective layer with aluminum nitride as the main component is covered on its surface. Combined with a conductive member, a wafer support with excellent corrosion resistance is formed by integrated sintering.

Benefits of technology

The corrosion resistance and heat impact resistance of the wafer support are improved, the generation of particles is reduced, the equipment life is extended and the stability of semiconductor manufacturing is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120569358A_ABST
    Figure CN120569358A_ABST
Patent Text Reader

Abstract

A wafer support (30) is provided with a base material (14) formed of a machinable ceramic containing boron nitride, a first layer covering the surface of the base material, and conductive members (18, 20) at least partially enclosed in the base material. The first layer is composed of a ceramic sintered body having aluminum nitride as the main component, and the ratio of boron nitride contained in the base material (14) is higher than the ratio of boron nitride contained in the first layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a support body for supporting a wafer. Background Art

[0002] Ceramic materials used in conventional electrostatic chucks, etc., are often fine ceramics such as silicon nitride or aluminum nitride, which are difficult to machine. Complex machining is difficult due to cutting speed and chipping (defects). Therefore, it is considered to use machinable ceramics with excellent machinability for the wafer support substrate (see Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2020-155571 Summary of the Invention

[0006] Problems to be solved by the invention

[0007] When the wafer support is exposed to the corrosive gas or plasma environment of the semiconductor manufacturing process, particles are easily generated from its surface. If these particles adhere to the wafer, they can cause problems in subsequent semiconductor manufacturing processes. Therefore, one solution is to cover the machinable ceramic substrate with a thin film of aluminum nitride, which is less corrosive due to plasma.

[0008] However, when corrosion originates from microscopic defects such as pinholes present in the aluminum nitride film, if the corrosion reaches the machinable ceramic as the substrate, the substrate is significantly corroded, generating particles and causing defective products.

[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a novel wafer support body having excellent corrosion resistance.

[0010] Solutions for solving problems

[0011] To address the above-mentioned issues, a wafer support according to one embodiment of the present invention comprises a substrate formed of a machinable ceramic containing boron nitride, a first layer covering the surface of the substrate, and a conductive member at least partially enclosed within the substrate. The first layer is composed of a ceramic sintered body containing aluminum nitride as a main component, and the proportion of boron nitride contained in the substrate is higher than the proportion of boron nitride contained in the first layer.

[0012] Machinable ceramics are easier to process than general fine ceramics and also have excellent thermal shock resistance. On the other hand, from the perspective of corrosion resistance, machinable ceramics such as boron nitride are not necessarily the best materials. Therefore, using this method, even if complex shapes cannot be achieved during the substrate fabrication stage, processing can be performed after the substrate is fabricated, enabling the production of wafer supports with diverse shapes. Furthermore, this method reduces corrosion caused by process gases and plasma on the substrate through the first layer.

[0013] The thickness of the first layer may be 0.3 to 3.0 mm. Thus, even if there are microscopic defects such as pinholes in the first layer, corrosion is unlikely to reach the substrate.

[0014] The first layer may contain 90 to 100% by mass of aluminum nitride and 0 to 10% by mass of boron nitride, thereby improving the corrosion resistance of the first layer.

[0015] A second layer may also be provided to cover the first layer. The second layer may be made of at least one material selected from the group consisting of aluminum nitride, aluminum oxide, yttrium oxide, and magnesium oxide, and may have a thickness of 1.0 to 20 μm. This can further improve the corrosion resistance of the substrate compared to the case of only the first layer.

[0016] The thermal expansion coefficient of the substrate is set to Δ1[1×10 -6 / ℃], the thermal expansion coefficient of the first layer is Δ2[1×10 -6 / °C], |Δ2-Δ1|≤1.0. Thus, the substrate and the first layer can be manufactured by integral sintering.

[0017] The machinable ceramic may contain 15-40 mass% of boron nitride, 0-40 mass% of zirconium oxide, 0-55 mass% of silicon nitride, 0-20 mass% of silicon carbide, and 0-75 mass% of aluminum nitride, based on the total of the ceramic components of boron nitride, zirconium oxide, silicon nitride, silicon carbide, and aluminum nitride being 100 mass%. It may also contain 3-15 mass% of a sintering aid component, based on the total of the ceramic components being 100 mass%.

[0018] The conductive member may be composed of a metal material selected from the group consisting of molybdenum, tungsten, tantalum, and alloys thereof.

[0019] However, any combination of the above components and any method, device, system, or other method of expressing the present invention are also valid as embodiments of the present invention. In addition, any combination of the above components may also be included in the scope of the invention protected by the present patent application.

[0020] Effects of the Invention

[0021] According to the present invention, a novel wafer support body having excellent corrosion resistance can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] [ Figure 1 ] is a schematic cross-sectional view of a wafer support body of a reference example.

[0023] [ Figure 2 ] is a schematic diagram used to illustrate the corrosion situation caused when there are defects in the protective layer.

[0024] [ Figure 3 ] is a diagram showing a photograph of a cross section of a wafer support having defects in an AlN film, taken using a scanning electron microscope (SEM).

[0025] [ Figure 4 ] is a schematic cross-sectional view of the wafer support body of this embodiment.

[0026] [ Figure 5 ] Figure 5 (a)~ Figure 5 (e) is a diagram showing an example of a method for manufacturing a wafer support body according to this embodiment.

[0027] [ Figure 6 ] Figure 6 (a) is a photograph showing a cross section of the protective layer of the aluminum nitride sintered body of Example 1 taken with a scanning electron microscope (SEM). Figure 6 (b) is a photograph showing a cross section of the protective layer of the aluminum nitride sintered body of Example 3 taken with a scanning electron microscope. Figure 6 (c) is a diagram showing a photograph of a cross section of an aluminum nitride thin film of a reference example taken with a scanning electron microscope.

[0028] [ Figure 7 ] Figure 7 (a) is a photograph showing the surface of the protective layer of the aluminum nitride sintered body of Example 1 taken with a scanning electron microscope (SEM). Figure 7 (b) is a photograph showing the surface of the protective layer of the aluminum nitride sintered body of Example 3 taken with a scanning electron microscope. Figure 7 (c) is a photograph of the surface of the aluminum nitride thin film of the reference example taken with a scanning electron microscope. Figure 7 (d) means Figure 7 The photo (a) is converted into an image using image analysis software. Figure 7 (e) means Figure 7 (b) is a diagram of an image converted using image analysis software. Figure 7 (f) means Figure 7 (c) is a diagram of an image converted using image analysis software.

[0029] [ Figure 8 ] Figure 8 (a)~ Figure 8 (c) is a schematic diagram for explaining the plasma exposure test. DETAILED DESCRIPTION

[0030] Hereinafter, the embodiment of the present invention will be described in detail with reference to the accompanying drawings. However, in the description of the drawings, the same elements are given the same reference numerals, and repeated descriptions are omitted as appropriate.

[0031] (Wafer support)

[0032] First, the general structure of a wafer support will be described as a reference example. A wafer support can be any support capable of supporting a semiconductor substrate such as a silicon wafer and may include an adsorption mechanism or a heating mechanism. For example, a wafer support may be a base that simply carries a wafer. Alternatively, a wafer support may be an electrostatic chuck that generates an adsorption force for the carried wafer, or a heater that heats the wafer. Furthermore, while the object supported by the wafer support is primarily a wafer, other components or parts may also be supported.

[0033] In the reference example, a case where the wafer support body is an electrostatic chuck with a heater will be described as an example. Figure 1 This is a schematic cross-sectional view of a wafer support body of a reference example.

[0034] A wafer support 10 of the reference example is used to support a wafer W within a chamber 12 of a semiconductor manufacturing apparatus such as a plasma CVD device. The wafer support 10 includes a base 14 formed of a machinable ceramic, a protective layer 16 covering a surface 14a of the base 14, and conductive members 18 and 20 at least partially enclosed within the base 14. The wafer W is mounted on the surface of the protective layer 16, which serves as a mounting surface 16a.

[0035] The conductive member 18 acts as an electrostatic chuck electrode for generating a current flow for the adsorption force used to fix the wafer W to the mounting surface 16a. In addition, the conductive member 20 acts as a resistance heating body (heater) for heating the wafer W to a specific process temperature. However, in the wafer support body 10 of this embodiment, the conductive members 18 and 20 are buried in the base material 14 which is a sintered body. For this reason, the conductive members 18 and 20 need to be arranged inside the raw material powder during the firing stage, and are preferably made of a high melting point metal that does not melt at the firing temperature. For example, as the material of the conductive member, high melting point metals such as molybdenum, tungsten, tantalum, or alloys containing two or more of these metals are preferred.

[0036] The wafer support 10 may also be provided with a gas inlet 22 connected to an external gas supply source (not shown) from the mounting surface 16a exposed to the chamber side through the interior of the substrate 14. The gas inlet 22 is used to supply gas to cool the wafer W adsorbed on the mounting surface 16a from the back side.

[0037] (machinable ceramics)

[0038] The present inventors have conducted continuous research to find a material suitable for the wafer support and have found that a sintered body made of so-called machinable ceramics having good machinability (free-machining properties) is preferable.

[0039] Machinable ceramics are easier to machine than conventional fine ceramics, such as alumina, silicon nitride, aluminum nitride, and silicon carbide. Specifically, machinable ceramics are less susceptible to chipping, a common problem in ceramic machining, allowing for complex machining. Furthermore, the grinding volume (processing rate) during machining of machinable ceramics can be several to hundreds of times greater than that of fine ceramics, enabling efficient machining.

[0040] Machinable ceramics are composite materials of various raw material compounds mixed to form ceramic components. For example, the volume resistivity can be adjusted by adjusting the mixing ratio of silicon carbide. As a result, it can correspond to either the adsorption mechanism of a Coulomb type or a Johnson-Rahbek (JR) type electrostatic chuck. In addition, in the case of a heater, by not adding silicon carbide, it can be used as an insulator. However, the machinable ceramic does not need to have a uniform composition as a whole. The composition can be made different in a manner that optimizes the function of each part, such as in a portion that accommodates the conductive member 18 close to the mounting surface 16a on which the wafer W is mounted and a portion that accommodates the conductive member 20.

[0041] Furthermore, boron nitride is cited as one of the main components. Compared with general aluminum oxide, silicon nitride, aluminum nitride, and silicon carbide, it has excellent thermal shock resistance and can prevent damage caused by cracks when used as a wafer support for a product.

[0042] The machinable ceramics of the reference examples and the embodiments described later are sintered bodies formed of at least two or more materials having boron nitride as an essential component selected from the group consisting of boron nitride, zirconium oxide, silicon nitride, silicon carbide, and aluminum nitride. Boron nitride also has excellent machinability, and the use of machinable ceramics having boron nitride as an essential component can increase the processing rate. In addition, when a wafer support body having a conductive component made of a different material is enclosed within a substrate, internal stress is generated due to temperature changes due to the difference in physical properties between the substrate and the conductive component. In addition, thermal stress is generated due to the temperature difference between the periphery and the center of the wafer support body. However, boron nitride has excellent thermal shock resistance, so the substrate is difficult to break.

[0043] Regarding the machinable ceramics of the reference example, when the total of the ceramic components of boron nitride, zirconium oxide, silicon nitride and silicon carbide is set to 100 mass%, it is appropriate to contain 10 to 80 mass% of boron nitride, 0 to 80 mass% of silicon nitride, 0 to 80 mass% of zirconium oxide, and 0 to 40 mass% of silicon carbide.

[0044] The machinable ceramics of the reference examples and embodiments described below contain a sintering aid component. The sintering aid can be selected from those used for sintering silicon nitride or boron nitride. Preferred sintering aids are one or more of aluminum oxide, magnesium oxide, yttrium oxide, and lanthanide metal oxides. More preferred are mixtures of aluminum oxide and yttrium oxide, mixtures further containing magnesium oxide, or mixtures of yttrium oxide and magnesium oxide.

[0045] Regarding the amount of the sintering aid component mixed, when the total amount of the ceramic component is set to 100 mass%, a range of 1 to 25 mass%, preferably 3 to 15 mass%, and more preferably 5 to 10 mass% is desirable as an external addition. When the amount of the sintering aid component mixed is 1 mass% or more, preferably 3 mass% or more, densification is facilitated, which can suppress insufficient density of the sintered body or a decrease in mechanical properties. On the other hand, when the amount of the sintering aid component mixed is 25 mass% or less, due to the reduction of low-strength grain boundary phases, a decrease in mechanical strength or a decrease in workability caused by an increase in grain boundary phases can be suppressed.

[0046] However, although boron nitride has excellent machinability, its strength characteristics are poor. Therefore, when there is coarse boron nitride in the sintered body, it becomes the starting point of destruction and becomes the main cause of defects and cracks during processing. In order to prevent the formation of such coarse boron nitride particles, it is effective to make the raw material powder into a fine powder. The main raw material powder, especially the raw material powder of boron nitride, is expected to use an average particle size of less than 2μm. Although boron nitride exists in hexagonal (h-BN) low-pressure phase or cubic (c-BN) high-pressure phase, hexagonal boron nitride is preferred from the perspective of fast machinability. In addition, from the perspective of machinability, the more boron nitride, the less silicon nitride (and zirconium oxide), the better. In addition, the more boron nitride, the less silicon nitride (and zirconium oxide), the lower the mechanical strength or Young's modulus.

[0047] As machinable ceramics, for example, BN-containing silicon nitride ceramics ("Photoveel II", "PhotoveelII-k70": manufactured by Ferrotec Material Technologies Co., Ltd.) can be cited. However, the composition of Photoveel II-k70 is as follows: 38.5% by mass of boron nitride, 54.1% by mass of silicon nitride, 5.5% by mass of yttrium oxide, and 1.9% by mass of magnesium oxide. The bending strength of this BN-containing silicon nitride ceramic is less than 600 MPa, the Young's modulus is less than 250 GPa, and the Vickers hardness is less than 5 GPa. With respect to machinable ceramics having such characteristics, the amount of grinding per unit time (machining rate) during processing is large, and even wafer supports of complex shapes can be efficiently produced. In addition, after the substrate is made into a block of a simple shape, it is cut into the desired shape and a complex wafer support is manufactured in the form of a part.

[0048] (Method for producing sintered body)

[0049] First, a raw material powder is prepared by mixing a main raw material powder of a ceramic component such as boron nitride, zirconium oxide, silicon nitride, silicon carbide, and aluminum nitride in a predetermined proportion with a sintering aid powder in an amount of 1 to 25% by mass relative to 100% by mass of the total ceramic component. This mixing can be performed, for example, using a wet ball mill.

[0050] Next, the raw material powder or the molded body or both are formed and fired under high temperature and pressure to produce a sintered body. However, a portion of the raw material powder or the molded body may be replaced by the sintered body. In addition, in order to place the resistance heating body for the heater or the electrode of the electrostatic chuck inside the sintered body, when the raw material powder, the molded body or the sintered body is filled in the heating and pressing device, the component or material that will become the conductor after firing (for example, a metal plate, metal foil, conductive paste, coil, mesh, etc.) can be arranged (buried) in a specific position. However, the shape of the conductor is not particularly limited. This firing can be carried out using a heating and pressing device, for example. Although heating and pressing are carried out in a non-oxidizing (inactive) environment such as a nitrogen or argon environment, it can also be carried out in pressurized nitrogen. The heating and pressing temperature is, for example, in the range of 1300 to 1950°C. When the temperature is too low, sintering is insufficient, and when it is too high, thermal decomposition of the main raw material will occur. The pressure is appropriately in the range of 20 to 50 MPa. The duration of heating and pressing varies depending on the temperature and size, but is generally about 1 to 4 hours. High-temperature pressure sintering can also be performed by HIP (hot isostatic pressing). The sintering conditions in this case can also be appropriately set by those skilled in the art.

[0051] Afterwards, the sintered body is processed into the desired shape to manufacture a wafer support. The machinable ceramics of the reference examples and embodiments have high strength and high machinability (fast cutting), and therefore, can be subjected to complex micro-machining in an industrially realistic time. In addition, the conditions for manufacturing the sintered body are to take into account the corrosion resistance caused by the plasma described later, and the average crystal grain size of the machinable ceramic is selected to be less than 0.5 μm. Thus, even if a part of the polycrystalline is peeled off as microparticles due to corrosion in the plasma environment, since the microparticles themselves are small, defects in the semiconductor manufacturing process can be reduced. However, the average crystal grain size of the machinable ceramic is more preferably less than 0.1 μm.

[0052] As described above, the machinable ceramic used in the reference example substrate 14 is easier to process than general fine ceramics. According to this method, even if a complex shape is not achieved during the substrate 14 fabrication stage, processing can be performed after fabrication, thereby enabling the manufacture of wafer supports of various shapes.

[0053] On the other hand, the wafer support 10 is exposed to corrosive gases or plasma environments during semiconductor manufacturing processes, depending on its intended use. Examples of corrosive plasmas include fluorine-based gases such as CF4, C4F8, SF8, NF3, and CHF3. Other corrosive gases may also be mixed with gases such as Ar, O2, and CO2. Silicon components are highly reactive with fluorine-based plasmas, so silicon-containing substrates have low resistance to these plasmas. Furthermore, boron nitride is highly reactive with O2 plasma.

[0054] As previously mentioned, the main components of the machinable ceramics of the reference examples may include silicon nitride, silicon carbide, or boron nitride. The inventors of this application have determined that machinable ceramics containing silicon or boron nitride may have reduced corrosion resistance in corrosive plasma environments. Furthermore, to enhance the corrosion resistance of the wafer support against plasma or process gases, a protective layer 16 is provided on the surface of the substrate 14 of the wafer support 10 of this embodiment.

[0055] (Protective layer)

[0056] The protective layer 16 of the reference example is made of a material that is less corroded by plasma than the substrate 14. Thus, the corrosion of the substrate 14 by plasma can be reduced by the protective layer 16. In addition, even if the material constituting the substrate 14 is easily peeled off, the peeling can be reduced by the protective layer 16. The protective layer 16 of the present embodiment is made of a material selected from aluminum nitride, aluminum oxide, yttrium oxide, magnesium oxide, yttrium aluminum garnet (YAG: Y3O5Al 12 ) and yttrium aluminum monoclinic (YAM: Y4Al2O9). Aluminum nitride, in particular, has excellent thermal shock resistance and is therefore a suitable material for processes that subject electrostatic chucks to high thermal shock.

[0057] like Figure 1 As shown, the thickness between the mounting surface 16a of the surface of the protective layer 16 and the conductive member 18 becomes the thickness t of the dielectric layer. Therefore, when the thickness of the protective layer 16 is too thick, the thickness t of the dielectric layer becomes large, and sufficient adsorption force cannot be obtained. In addition, when the thickness t is too large, cracks are easily generated in the protective layer 16 when a high thermal shock is applied. On the other hand, when the thickness t of the protective layer 16 is too small, sufficient corrosion resistance to plasma cannot be obtained. Here, the thickness of the protective layer 16 of the reference example is in the range of 1 to 30 μm. In this way, the desired adsorption force and corrosion resistance to plasma can be achieved. When the thickness of the protective layer 16 is preferably 2 μm or more, more preferably 5 μm or more, better corrosion resistance to plasma can be obtained. In addition, when the thickness of the protective layer 16 is preferably 20 μm or less, more preferably 10 μm or less, more sufficient adsorption force can be obtained.

[0058] (Method for forming protective layer)

[0059] The protective layer is formed by methods such as CVD, PVD (sputtering or ion plating), and aerosol deposition. These methods are excellent in controlling film thickness, and thus, as described above, the protective layer can be formed with high precision in a thickness range of 1 to 30 μm.

[0060] Regarding sputtering, the substrate and the target (the material to be the film) are placed opposite each other. -1 In an Ar gas atmosphere of approximately several Pa, a negative high voltage is applied to the target to discharge, causing Ar ions to collide with the target. When the Ar ions collide, atoms are ejected from the target through sputtering. The sputtered atoms accumulate on the substrate, forming a protective layer.

[0061] Reactive sputtering is suitable for forming the protective layer 16 of the reference example. When compounds such as aluminum oxide or aluminum nitride are used as targets, the sputtering rate significantly decreases, resulting in a significantly reduced coating speed and, as a result, varying sputtering rates for each element, leading to the formation of a film that deviates from the target composition. Therefore, when the protective layer of the reference example is made of aluminum nitride, a reactive sputtering method using a single-metal aluminum target and reacting with the reactive gas N2 is suitable.

[0062] Ion plating, another method of forming a protective layer, is to place a substrate and an evaporation source (the material to be formed into the film) opposite each other and -2 ~10 -4A method of dissolving / evaporating the raw material of the film from an evaporation source in a vacuum of about Pa and depositing it on a substrate. Films of various materials can be made by changing the type of evaporated material or the introduction of reactive gas. In the coating technology based on vacuum evaporation, the method of using ions is generally referred to as ion plating. Specifically, although there are various methods such as high-frequency ion plating, reactive ion plating, and ion-assisted evaporation, all of them can be adopted. When the constituent material of the protective layer of the reference example is yttrium oxide, metal yttrium can be used in the evaporation source, O2 can be introduced into the reactive gas, and film formation can be performed in a plasma environment. In addition, during ion-assisted evaporation, by using yttrium oxide as the evaporation source and O2 ions as the auxiliary ions, a protective layer whose constituent material is yttrium oxide can be formed. However, when the constituent material of the protective layer is magnesium oxide or aluminum oxide, film formation can also be performed by high-frequency ion plating, reactive ion plating, and ion-assisted evaporation.

[0063] When using ion film forming methods such as the aforementioned sputtering or ion plating, the surface can be cleaned with Ar ions before film formation (surface attachments or oxide films are removed by ion impact), thereby obtaining a film with high adhesion. N2 ions or H2 ions are particularly effective in cleaning organic matter (generally referred to as an ion bombardment process). Through the bombardment process, extremely fine particles (which cannot be completely removed by ultrasonic cleaning, etc.) on the surface of the machinable ceramic substrate can be removed. Therefore, the substrate with a protective film can reduce the initial generation of particles compared to the substrate without a protective film. Compared with bulk ceramics made by sintering powder, these methods can also improve the purity of aluminum nitride, so the concern about wafer contamination is also reduced, which helps to reduce defects.

[0064] In addition, regarding the electrostatic chuck using a substrate made of machinable ceramic, when the surface roughness of the substrate is within a specific range (for example, the range of arithmetic mean roughness Ra of 0.02μm≤Ra≤0.2μm), there is less friction with the wafer during desorption (dechuck) because it makes point contact with the wafer. On the other hand, due to the cleavage property of boron nitride, particles are easily peeled off (cracked) by physical force, so if this state is maintained, microparticles are easily generated. However, by applying the protective layer 16 of aluminum nitride or the like described above to the surface of the substrate 14, the peeling of particles can be reduced, and the generation of microparticles can be reduced. In addition, the protective layer 16 produced by the film forming method of the reference example follows the surface roughness of the substrate 14 and has a surface with an arithmetic mean roughness Ra of 0.02μm≤Ra≤0.2μm. That is, since the protective layer 16 is resistant to plasma corrosion and the protective layer 16 itself can make point contact with the wafer, the wafer support body 10 of the reference example is extremely excellent in reducing microparticles.

[0065] In addition, when the multilayer component is composed of each layer of a hard material (a combination of materials with a high Young's modulus), any layer is difficult to deform and is therefore prone to cracking due to thermal stress or the like. However, as in the wafer support 10 of the reference example, by using a substrate 14 containing boron nitride as a main component, stress can be absorbed (relaxed). In addition, the machinable ceramic of the reference example is a composite material, so the thermal expansion coefficient of the substrate 14 can be made consistent with the thermal expansion coefficient of the protective layer 16. As a result, the thermal stress caused by the difference in thermal expansion coefficient of each layer can be reduced, and the generation of cracks can be suppressed, that is, the generation of particles can be suppressed.

[0066] The wafer support of the reference example has excellent thermal shock resistance characteristic of machinable ceramics and can also improve corrosion resistance to plasma and process gases via the protective layer 16. However, the inventors have considered that the following problems may occur if microscopic defects such as pinholes (small holes) exist in the AlN film serving as the protective layer. Figure 2 This is a schematic diagram used to illustrate the corrosion that occurs when there are defects in the protective layer. Figure 3 The figure shows a photograph of a cross section of a wafer support body having defects in an AlN film, taken with a scanning electron microscope (SEM).

[0067] like Figure 2 、 Figure 3 As shown, if corrosion originates from a defect, it will significantly corrode the machinable ceramic substrate if it reaches it. This results in the generation of particles, leading to defective products. Furthermore, with conventional film-forming technologies, it is extremely difficult to reduce the number of microscopic defects such as pinholes to zero. Furthermore, if the AlN film disappears due to overall corrosion, the machinable ceramic substrate, which has low corrosion resistance, is exposed to the front surface, generating a large number of particles. This not only results in defective products but also contaminates the equipment. This can lead to equipment failures and increased downtime.

[0068] Here, in the wafer support body of the present embodiment, a sintered body containing aluminum nitride as a main component is provided between the protective layer 16 and the base material 14 . Figure 4 This is a schematic cross-sectional view of the wafer support body of this embodiment. Figure 1 The same configuration as the wafer support body 10 of the reference example shown (conductive members 18 and 20 , gas introduction port 22 , etc.) is omitted from the illustration.

[0069] The wafer support 30 of this embodiment includes a substrate 14 formed of a machinable ceramic containing boron nitride, a protective layer 15 covering a surface 14a of the substrate 14, and conductive members 18 and 20 at least partially enclosed within the substrate 14. The protective layer 15 is composed of a ceramic sintered body containing aluminum nitride as a main component, and the proportion of boron nitride contained in the substrate 14 is higher than that in the protective layer 15. An intermediate layer containing a machinable ceramic as a main component may be provided between the protective layer 15 and the substrate 14.

[0070] Machinable ceramics are easier to process than general fine ceramics and also have excellent thermal shock resistance. Therefore, the wafer support 30 of this embodiment can be processed after the substrate 14 is manufactured, even if a complex shape is not achieved during the manufacturing stage. This allows for the manufacture of wafer supports of various shapes.

[0071] On the other hand, from the perspective of corrosion resistance, machinable ceramics such as boron nitride are not necessarily the best materials. Therefore, by further providing a protective layer 15 formed from a ceramic sintered body primarily composed of highly corrosion-resistant aluminum nitride on substrate 14, even if minor defects or loss of protective layer 16, formed from the thin film of aluminum nitride, occur, substrate 14 is less likely to be directly exposed to the corrosive atmosphere, thereby suppressing corrosion of substrate 14 by process gases or plasma. This results in a reduction in the amount of particles, reduces the occurrence of defects in the manufacturing process, and also achieves protection of semiconductor manufacturing equipment.

[0072] It should be noted that the thickness of the protective layer 15 can be in the range of 0.3 to 3.0 mm, more preferably in the range of 0.5 to 2.0 mm. Thus, even if there are tiny defects such as pinholes in the protective layer 15, corrosion is difficult to reach the substrate. It should be noted that when the thickness of the protective layer is too thin (for example, less than 0.3 mm), it is difficult to manufacture it in the form of a sintered body. In addition, in the presence of tiny defects, the holes are likely to penetrate into the substrate. On the other hand, if the thickness of the protective layer is too thick (for example, greater than 3.0 mm), the effect of improving the thermal shock resistance by stacking the machinable ceramic substrate 14 with the protective layer 15 of the inclined structure will disappear.

[0073] The protective layer 15 may contain 70-100% by mass of aluminum nitride and 0-30% by mass of boron nitride, or 80-100% by mass of aluminum nitride and 0-20% by mass of boron nitride, preferably 90-100% by mass of aluminum nitride and 0-10% by mass of boron nitride. In this way, the corrosion resistance of the protective layer 15 can be improved. It should be noted that, from the perspective of thermal shock resistance, the more boron nitride the protective layer 15 contains, the better. The finer the particle size of the aluminum nitride or boron nitride contained in the protective layer 15, the better the corrosion resistance. The average particle size is preferably 5 μm or less, and more preferably 2 μm or less. The fine particles generated by the fine particle size become smaller, which can reduce the defects of semiconductors manufactured by a device using a wafer support.

[0074] The wafer support body 30 of the present embodiment also includes a protective layer 16 covering the protective layer 15. The protective layer 16 of the present embodiment is selected from at least one material selected from the group consisting of aluminum nitride, aluminum oxide, yttrium oxide and magnesium oxide, and has a thickness of 1.0 to 20 μm. The thickness of the protective layer 16 is more preferably 1.0 to 10 mm. As a result, the corrosion resistance of the substrate 14 is further improved compared to the case of only the protective layer 15. It should be noted that when the protective layer 15 is too thin, the corrosion resistance becomes lower (the life of the component becomes shorter), and when the protective layer 15 is too thick, cracks are easily generated due to the internal stress during film formation.

[0075] Furthermore, by forming a thin film of aluminum nitride, such as protective layer 16, on the relatively thick protective layer 15 of the ceramic sintered body, even if protective layer 16 corrodes and the protective layer 15 of the underlying ceramic sintered body is exposed, the wafer support can be reused by re-forming protective layer 16. As a result, the life of the wafer support can be extended.

[0076] In the wafer support body 30 of this embodiment, the thermal expansion coefficient of the substrate 14 is set to Δ1 [1×10 -6 / °C], the thermal expansion coefficient of the protective layer 15 as the first layer is Δ2[1×10 -6 / ℃], |Δ2-Δ1|≤1.0 is satisfied. Thus, the substrate 14 and the protective layer 15 can be produced by integral sintering. It should be noted that when the value of |Δ2-Δ1| is large, the possibility of not being able to obtain a good integral sintered product increases due to the thermal stress during firing, such as cracks in either the substrate 14 or the protective layer 15. In particular, boron nitride is a material with a small Young's modulus and has the effect of alleviating thermal stress and inhibiting the generation of cracks. Therefore, it is effective for alleviating the mismatch of the characteristics of each layer. In addition, according to the integral sintering method, since a layer formed of a material with high thermal conductivity that cannot be produced by conventional machinable ceramics can be formed on the wafer contact surface or in the vicinity thereof, the thermal uniformity of the wafer in the semiconductor manufacturing process can be improved. Specifically, in conventional machinable ceramics, the thermal conductivity can only be achieved to about 70W / m·K, but by providing a ceramic sintered body with aluminum nitride as the main component as the protective layer 15 on the substrate 14, a thermal conductivity of 90W / m·K or more can be achieved.

[0077] It should be noted that when the difference in thermal expansion coefficients Δ between the substrate 14 and the protective layer 15 (Δ2-Δ1|) is greater than 1.0, an intermediate layer having a thermal expansion coefficient Δ3 between the thermal expansion coefficients Δ1 and Δ2 (Δ1<Δ3<Δ2 or Δ2<Δ3<Δ1) may be formed between the substrate 14 and the protective layer 15. In this case, the differences in thermal expansion coefficients |Δ1-Δ3| and |Δ2-Δ3| are both 1.0×10 -6 / ℃ or below is appropriate.

[0078] It should be noted that the machinable ceramic of the substrate of this embodiment may contain 15-40 mass% of boron nitride, 0-40 mass% of zirconium oxide, 0-50 mass% of silicon nitride, 0-20 mass% of silicon carbide, and 0-75 mass% of aluminum nitride, based on the total of the ceramic components of boron nitride, zirconium oxide, silicon nitride, silicon carbide, and aluminum nitride being 100 mass%. It may also contain 3-15 mass% of a sintering aid component, based on the total of the ceramic components being 100 mass%.

[0079] Figure 5 (a)~ Figure 5 (e) is a diagram showing an example of a method for manufacturing a wafer support body according to this embodiment. Figure 5 As shown in (a), a powder 32 having the composition of the base material 14 is filled into a hot press mold 34 and uniaxially pressed to form a first pressurized body 36 ( Figure 5 Then, the powder 38 having the composition of the protective layer 15 is filled on the first pressurizing body 36 and uniaxially pressed to form the second pressurizing body 40 ( Figure 5 (c)). The two-layered compact thus obtained is placed in a firing furnace 42 and subjected to hot pressing and firing ( Figure 5 (d)). Thus, the substrate 14 and the protective layer 15 are formed integrally, and then the protective layer 16 is formed on the protective layer 15 by CVD or PVD ( Figure 5 (e)).

[0080] It should be noted that after the powder 32 is filled into the mold 34, the powder 38 may be filled into the mold 34 from above while simultaneously performing uniaxial pressing. As another manufacturing method, a molded body formed by CIP (Cold Isostatic Pressing) of the powder 32 may be placed on a molded body formed by CIP (Cold Isostatic Pressing) of the powder 38 and hot pressed to form an integral mold.

[0081] [Example]

[0082] Next, the properties of the wafer support bodies of the Examples and Comparative Examples are described. The contents of the ceramic components and sintering aid components in the Examples and Comparative Examples are shown in Table 1. The film thickness was measured from cross-sectional photographs taken with a scanning electron microscope.

[0083] [Table 1]

[0084]

[0085] (Cross-section structure)

[0086] Figure 6 (a) is a photograph showing a cross section of the protective layer of the aluminum nitride sintered body of Example 1 taken with a scanning electron microscope (SEM). Figure 6 (b) is a photograph showing a cross section of the protective layer of the aluminum nitride sintered body of Example 3 taken with a scanning electron microscope. Figure 6 (c) is a photograph showing a cross section of an aluminum nitride thin film of a reference example taken with a scanning electron microscope.

[0087] Figure 6 (a) Figure 6 The protective layer 15 of the aluminum nitride sintered body shown in (b) is a structure filled with particles with a particle size of about 1 to 5 μm. Figure 6 The aluminum nitride film shown in (c) is formed by sputtering and is a structure filled with columnar particles less than 1 μm in size. As can be seen, there is a clear difference in structure between the sintered body and the thin film. In addition, by using the aluminum nitride sintered body as a tilting material, a protective layer 15 (corrosion-resistant layer) with a thickness that is difficult to achieve using the method of making aluminum nitride thin films can be formed. As a result, the durability of the wafer support body of this embodiment is improved (longer life).

[0088] The surface properties of the wafer support samples of Examples 1 to 5 and Comparative Examples 1 to 3 and the results of the plasma exposure test are shown in Table 2. The presence or absence of cracks was confirmed visually or with a microscope (×20 magnification).

[0089] [Table 2]

[0090]

[0091] (Surface characteristics of sample)

[0092] Figure 7 (a) is a photograph showing the surface of the protective layer of the aluminum nitride sintered body of Example 1 taken with a scanning electron microscope (SEM). Figure 7 (b) is a photograph showing the surface of the protective layer of the aluminum nitride sintered body of Example 3 taken with a scanning electron microscope. Figure 7 (c) is a diagram showing a photograph of the surface of the aluminum nitride thin film of the reference example taken with a scanning electron microscope. Figure 7 (d) means Figure 7 The photo (a) is converted into an image using image analysis software. Figure 7 (e) is Figure 7 (b) is a diagram of an image converted using image analysis software. Figure 7 (f) is Figure 7 (c) is a diagram of an image converted using image analysis software.

[0093] Here, Figure 7 (a)~ Figure 7 The magnification of the SEM photograph shown in (c) is 1000 times. In addition, for image analysis, the image analysis software (WIN ROOF) was used to extract the depressed portion and calculate the area ratio of the depressed portion. It should be noted that in order to extract a clear area ratio of the depressed portion, the image analysis software was used to calculate the area ratio of the depressed portion. 2 The following depressions are excluded from the calculation.

[0094] for Figure 7 (a) Figure 7 The surface of the aluminum nitride sintered body shown in (b) is Figure 7The surface of the aluminum nitride film shown in (c) has different shapes, sizes, and area ratios of the bumps. For example, the shape of the depressions (holes) on the surface of the aluminum nitride sintered body is that the edges stand up, while the shape of the depressions (holes) on the surface of the aluminum nitride film is that the edges do not stand up. In addition, the area ratio of the depressions on the surface of the aluminum nitride film (0.6%) is smaller than the area ratio of the depressions on the surface of the aluminum nitride sintered body. It should be noted that when there are many holes or the edges stand up, the surface area becomes larger and the part exposed to the corrosive gas increases, which is not conducive to corrosion resistance. Therefore, the smaller the area ratio, the better.

[0095] As the surface condition of the sample, the arithmetic mean roughness Ra specified in JIS B 0601 was measured. In addition, in Examples 1 to 5, the surface of the thin film corresponding to the protective layer 16 was measured.

[0096] (Plasma exposure test)

[0097] Figure 8 (a)~ Figure 8 (c) is a schematic diagram for explaining the plasma exposure test. The plasma generator used in the test is RIE-10N manufactured by SAMCO. The plasma output is 100W, and the gas species is a mixture of 40sccm CF4 and 10sccm O2. The pressure is 40Pa, and the processing time is 240 minutes (30 minutes × 8 times). Figure 8 As shown in (a), a mask 46 such as Kapton tape is attached to a portion of a test sample 44 simulating a wafer support. Figure 8 After a predetermined treatment time, the mask 46 is removed and the height difference d between the portion not covered by the mask 46 and the portion covered by the mask 46 is measured as the etching amount (refer to Figure 8 As shown in Table 2, the height difference d of the wafer support bodies of Examples 1 to 5 was 0 μm, and no corrosion was observed.

[0098] (Vickers hardness)

[0099] In addition to the aforementioned chemical etching, plasma corrosion resistance can also be affected by physical etching. For example, by including a material in the protective layer that is difficult to sublime even when reacting with a plasma containing a fluorine-based (CF4) gas (e.g., aluminum or yttrium), resistance to chemical corrosion can be improved. Furthermore, a high-hardness protective layer that is resistant to physical impact can be expected to provide even higher plasma corrosion resistance.

[0100] Therefore, the inventors of this application focused on the film hardness of the protective layer. The film hardness is measured using nanoindentation hardness (H_IT) and converted to Vickers hardness (GPa). For example, the wafer supports of Examples 1, 3, and 4 had Vickers hardnesses of 10 GPa or greater. Combined with the results of the plasma exposure test on the amount of corrosion, it is expected that they will have even higher corrosion resistance to plasma.

[0101] While the present invention has been described above with reference to embodiments or examples, the present invention is not limited to the aforementioned embodiments. Appropriate combinations or substitutions of the configurations of the embodiments are also encompassed by the present invention. Furthermore, based on the knowledge of those skilled in the art, appropriate substitutions of the combinations of the embodiments or the order of the processes, or various design modifications, etc., may be made to the embodiments, and such modified embodiments are also encompassed by the scope of the present invention.

[0102] Industrial applicability

[0103] The present invention can be used in an electrostatic chuck.

Claims

1. A wafer support, characterized in that: The invention comprises: a substrate formed of a machinable ceramic containing boron nitride, a first layer covering a surface of the substrate, and a conductive member at least partially enclosed in the substrate. The first layer is composed of a ceramic sintered body having aluminum nitride as a main component, The proportion of boron nitride contained in the base material is higher than the proportion of boron nitride contained in the first layer.

2. The wafer support according to claim 1, wherein The thickness of the first layer is 0.3 to 3.0 mm.

3. The wafer support according to claim 1 or 2, wherein: The first layer contains 90 to 100% by mass of aluminum nitride and 0 to 10% by mass of boron nitride.

4. The wafer support according to claim 1 or 2, wherein: further comprising a second layer covering the first layer, The second layer is made of at least one material selected from the group consisting of aluminum nitride, aluminum oxide, yttrium oxide, and magnesium oxide, and has a thickness of 1.0 to 20 μm.

5. The wafer support according to claim 1 or 2, wherein: The thermal expansion coefficient of the substrate is set to Δ1[1×10 -6 / °C], the thermal expansion coefficient of the first layer is set to Δ2[1×10 -6 / ℃], |Δ2-Δ1|≤1.

0.

6. The wafer support according to claim 1 or 2, wherein: The machinable ceramic contains 15-40% by mass of boron nitride, 0-40% by mass of zirconium oxide, 0-55% by mass of silicon nitride, 0-20% by mass of silicon carbide, and 0-75% by mass of aluminum nitride, when the total of the ceramic components of boron nitride, zirconium oxide, silicon nitride, silicon carbide, and aluminum nitride is set to 100% by mass. When the total amount of the ceramic components is 100% by mass, 3 to 15% by mass of a sintering aid component is further contained.

7. The wafer support according to claim 1 or 2, wherein: The conductive member is composed of a metal material selected from the group consisting of molybdenum, tungsten, tantalum, and alloys thereof.

Citation Information

Patent Citations

  • Wafer support and method for manufacturing wafer support

    JP2020155571A